Iterative surface warping to shape craters in micro-EDM simulation. (July 2016) - Surleraux, Anthony; Pernot, Jean-Philippe; Elkaseer, Ahmed; Bigot, Samuel
Abstract This paper introduces a new method for simulating the micro-EDM process in order to predict both the tool's wear and the workpiece's roughness. The tool and workpiece are defined by NURBS patches whose shapes result from an iterative crater-by-crater deformation technique driven by physical parameters. Through hundreds of thousands of local surface warping, the method is able to compute the global as well as the local shapes of the tool and workpiece. At each step, the warping vector and function are computed so as to be able to generate a spherical crater whose volume is also controlled. While acting very locally to simulate the real physical phenomenon, not only the method can evaluate the tool's wear from the overall final shape at a low resolution level, but it can also estimate the workpiece's roughness from the high resolution level. The simulation method is validated through a comparison with experimental data. Different simulations are presented with an increase in computation accuracy in order to study its influence on the results and their deviation from expected values.